PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V DI UPT SD NEGERI 081 HUTASOIT II - Tamba, Nurlela; Darinda Sofia Tanjung; Patri Janson Silaban; Regina Sipayung; Juliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Project Based Learning learning model on student learning outcomes in the subject of science on the material "Properties of Light" of grade V at UPT SD Negeri 081 Hutasoit II in the academic year of 2024/2025. The study used an experimental method with a quantitative approach, and involved 25 students as the total sample. The instruments used were questionnaires and multiple-choice tests.The results showed an average pretest score of 61.40 and a posttest of 78.90, with an average questionnaire score of 74.20. The correlation coefficient test showed a value of 0.968 ≥ 0.396 (r count ≥ r table), and the t-test showed t count ≥ t table (18.584 ≥ 2,069), which means Ha is accepted. Thus, there is a positive and significant influence of the Project Based Learning model on student learning outcomes.